2018
DOI: 10.5713/ajas.18.0154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod on nutrient digestibility, hair follicle activity and cashmere quality in Inner Mongolia white cashmere goats

Abstract: The cashmere production of Inner Mongolia white cashmere goats was increased without obvious deleterious effects on the cashmere fibers in the SDPP group (metabolizable energy: 8.34 MJ/kg, CP: 11.16 %, short daily photoperiod: 7 h Light:17 h Dark).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…In the current study, the population of primary hair follicles in the skin was the same for both melatonintreated and control cashmere goats and did not change over two consecutive cashmere growth cycles. This helps to con rm the view that the population of primary hair follicles in cashmere goats is established at birth and is not affected subsequently by treatment of adult cashmere goats with exogenous melatonin [8,[17][18][19]. In the case of secondary hair follicles, previous studies have also shown no effect of melatonin treatment on their total population, and thus no effect on S:P ratio [20,21].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the current study, the population of primary hair follicles in the skin was the same for both melatonintreated and control cashmere goats and did not change over two consecutive cashmere growth cycles. This helps to con rm the view that the population of primary hair follicles in cashmere goats is established at birth and is not affected subsequently by treatment of adult cashmere goats with exogenous melatonin [8,[17][18][19]. In the case of secondary hair follicles, previous studies have also shown no effect of melatonin treatment on their total population, and thus no effect on S:P ratio [20,21].…”
Section: Discussionsupporting
confidence: 54%
“…Although melatonin treatment of adult cashmere goats does not affect the total population of secondary hair follicles, it does increase the population that is active [20,21,24], as does exposure of goats to arti cial short-day photoperiods [11,18,25]. This indicates that melatonin treatment speeds up the transition of secondary hair follicles from telogen to the anagen phase, thus promoting onset of their activity.…”
Section: Discussionmentioning
confidence: 99%
“…All the goats were housed in individual pens and were fed diets twice a day at 09:00 hr and 15:00 hr, and the goats had free access to water and a mineral mixture block. The diet and remaining feed of each goat were weighed in order to determine the goat's dry matter intake (DMI) (Zhang, Sun, Li, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In order to minimize goats' suffering, all skin tissue samples were collected under local procaine hydrochloride anesthesia according to the International Guiding Principles for Biomedical Research Involving Animals. The Animal Ethics Committee of the Inner Mongolia Academy of Agriculture and Animal Husbandry Sciences (Hohhot, China), which is responsible for Animal Care and Use in the Inner Mongolia Autonomous Region of China, approved the experimental protocols used in this study (approval number IMAAAHS#1215000046002373XP) (Zhang, Sun, Li, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Cashmere goats harbor two different kinds of fleece: A short and fine nonmedullated cashmere fiber, which is produced by a secondary hair follicle (SHF), and a long and coarse medullated guard hair, which is produced by a primary hair follicle (PHF) [8]. Hair follicle (HF) growth, which is a highly orchestrated and cyclic process, involves three main stages: Anagen (the rapid growth phase, from April until November), catagen (the gradual degeneration phase, from December to January), and telogen (the relative static phase, from February to March) [9][10][11][12][13]. Although the hair follicle cycle stage of cashmere goat has a unique length and duration, the basic principle of the cyclic transformations of hair follicles is similar to other mammals.…”
Section: Introductionmentioning
confidence: 99%